Convergent Lady Beetle Hippodamia convergens Guérin-Méneville (Insecta: Coleoptera: Coccinellidae) - Luis F. Aristizábal; Steven P. Arthurs (EDIS)
The convergent lady beetle, Hippodamia convergens Guérin-Méneville, is among the most common lady beetle species throughout North America and is an important natural enemy of aphids, scales, thrips, and other soft-bodied insects. It will also feed on pollen and nectar from flowers when prey is scarce. This species can be found in habitats ranging from grasslands, forests, agricultural fields, gardens, and natural parks. It is one of the few natural enemies that are currently wild-collected from mass aggregations for distribution to the pest control industry. This 5-page fact sheet was written by Luis F. Aristizábal and Steven P. Arthurs, and published by the UF Department of Entomology and Nematology, June 2014.